Power over Fiber for Phone Charging Application - Amin E.P.P.; Noorazmin N.A.; Lee H.J.; Ker P.J.; Jamaludin M.Z.; Awang R.; Yusof F.A.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
5G mobile communication systems; Conversion efficiency; Inductive power transmission; Light transmission; Transmissions; Emerging technologies; Energy; Fiber applications; Multimodes; Power delivery; Power over fiber; Power system efficiency; Power-transmission; Smart phones; Smartphone charging; Multimode fibers